Returns to education and wages in Turkey: robust and resistant regression - ÇAĞLAYAN AKAY, EBRU; GÜRİŞ, SELAHATTİN (SPRINGER, 2012)
In this study, we follow the human capital theory for wage determination and analyze the differentials in returns to education, returns to experience and gender wage gap using usual mincerian wage equation by using OLS, robust and resistant regressions. This study presents evidence on the returns to education in Turkey. The results clearly show that for female employees, education to returns is higher than for male employees. When the results of returns to experience have been studied, it is observed that males definitely have a higher return than females in the years 2003 and 2006.
Keywords: Education; Wage; Mincerian equation; Robust regression; Resistant regression; QUANTILE REGRESSION; UNITED-STATES